Design and simulation of wireless power transfer using capacitive technique / Nur Fatin Afiqah Ahmad - Nur Fatin Afiqah, Ahmad (2021)
The development of wireless power transfer technology in various applications has getting widely nowadays. Wireless energy can be transferred by inductive power transfer (IPT) through electric field and capacitive power transfer (CPT) through magnetic field. Most of the applications has been utilized the technology of IPT for transfering power wirelessly, but in this project, a new method of CPT will be used for the purposed of biomedical implantable application which is implantable pulse generator (IPG). In terms of biomedical implantable application, CPT has some extra advantages compared to the traditional method of IPT such as the circuit structured will be more simple and convenient as the receiver circuit for this application will be implanted inside of the human body. Besides, the main reasons to use CPT technique are CPT has low electromagnetic interference (EMI), power losses is low and the ability of CPT to transfer power across metal barriers. In this project, the CPT technique has been applied through class E inverter circuit. A 12V DC source has been supplied to the inverter circuit that will operate at 1 MHz frequency to deliver 2 Watt of power to the load. The effects of higher load resistance values will be analyzed through the class E circuit system and the improvement of class E circuit by impedance matching will be applied. Overall, class E circuit is able to achieve ZVS waveform and efficiency of 95.38% by Matlab simulation for the resistance load value that have been designed theoretically. As the resistance value is set to some higher random values, class E circuit could only achieve ZVS and efficiency of more than 90% with the improvement by impedance matching circuit.